Modifying Factors and Level of Knowledge About Pregnancy Danger Signs That Influence Antenatal Care Utilization Compliance - Shofa Ilmiah, Widia; Sulistiyah (Jurnal Ilmiah Kesehatan, 2024)
The 3rd Sustainable Development Goal (SDG) is to guarantee healthy lives and to promote well-being. Reducing the maternal mortality ratio (MMR) to 70 per 100,000 live births is one of the SDG's primary metrics. In Indonesia, 74.1% of expectant mothers had at least four antenatal care (ANC) appointments in 2018, while 70.67% of mothers finished six ANC visits in 2022. The percentage was 74.92% in East Java, while the coverage in Nganjuk Regency decreased slightly from 79.90% in 2017 to 77.92% in 2019. The purpose of this research was to examine the moderating variables and the impact of pregnancy risk sign information on ANC use compliance. The study included all 53 pregnant women in the community and used a quantitative, cross- sectional, analytic correlation design. Total sampling, questionnaires, MCH books, and observation sheets were used as data-collecting techniques. A study of binary logistic regression was used. According to the findings, there was no discernible impact of schooling on ANC compliance (p = 0.546). ANC compliance was, however, substantially correlated with knowledge (p = 0.050; PR = 7.099), gestational age (p = 0.005; PR = 0.023), parity (p = 0.020; PR = 0.089), and information (p = 0.029; PR = 0.051). Notably, ANC adherence was seven times more impacted by knowledge level. Six ANC visits must be completed to identify and avoid issues early on, which emphasizes the need to raise pregnant women's knowledge in order to increase compliance.